Novel Tetracyclines Versus Alternative Antibiotics for Treating Acute Bacterial Infection: A Meta-Analysis of Randomized Controlled Trials - Shao-Huan Lan; Wei-Ting Lin; Shen-Peng Chang; Li-Chin Lu; Chih-Cheng Lai; Jui-Hsiang Wang; Chien-Ming Chao (Antibiotics, 2019)
This meta-analysis assessed the efficacy and safety of novel tetracyclines for treating acute bacterial infections. Data from PubMed, Web of Science, EBSCO, Cochrane databases, Ovid Medline, and Embase databases were accessed until 11 July 2019. Only randomized controlled trials (RCTs) comparing the efficacy of novel tetracyclines with that of other antibiotics for treating acute bacterial infections were included. Primary outcomes included the clinical response, microbiological response, and risk of adverse events (AEs). A total of eight RCTs were included, involving 2283 and 2197 patients who received novel tetracyclines and comparators, respectively. Overall, no significant difference was observed in the clinical response rate at test of cure between the experimental and control groups (for modified intent-to-treat [MITT] population, risk ratio [RR]: 1.02, 95% confidence interval [CI]: 0.99−1.05; for clinically evaluable [CE] population, RR: 1.02, 95% CI: 1.00−1.04; and for microbiological evaluable [ME] population, RR: 1.01, 95% CI: 0.99−1.04). No significant difference in the microbiological response at the end of treatment was observed between the experimental and control groups (for ME population, RR: 1.01, 95% CI: 0.99−1.03; for microbiological MITT population, RR: 1.01, 95% CI: 0.96−1.07). No difference was observed concerning the risk of treatment-emergent adverse events (TEAEs), serious adverse events, and discontinuation of treatment due to TEAEs and all-cause mortality between the two groups. In conclusion, clinical efficacy and safety profile for novel tetracyclines in the treatment of acute bacterial infections were found to be similar to those for other available antibiotics.